Use of minimally invasive gingival biopsies in the study of inflammatory mediators expression and their correlation with gingival fluid in patients with chronic periodontitis - Karina Schittine Bezerra Lomba; Tatiane Flôr Coelho de Souza Breves Beiler; Manuela Rubim Camara Sete; Fábio Ramoa Pires; Carlos Marcelo da Silva Figueredo (Indian Journal of Dental Research, 2015)
Background: There are no studies comparing the gingival crevicular fluid (GCF) cytokines expression with its corresponding values from the same tissue′s sites. Such comparison might be of great value since most of the cytokine function is related to cell and/or tissue receptors. Aims: Our aim was to use minimally invasive biopsies to evaluate the expression of interferon-gamma, interleukin 1 (IL-1) β, IL-6, IL-17A, IL-17F, and their correlation with the expression in gingival fluid in patients with chronic periodontitis. Materials and Methods: The collection of gingival fluid comprised 22 samples from 11 patients (mean age 46.73 ± 10.16 standard deviation years) with chronic periodontitis. The collection of biopsies comprised 22 samples from the same patients. Gingival fluid and biopsy were taken from the same site in one shallow and one deep site per patient. Gingival fluid samples were collected with periopaper ® and analyzed using Luminex ® . Biopsies were taken with a 2 mm diameter punch and analyzed for the same mediators using immunohistochemistry. Results: The gingival fluid showed higher amounts for IL-1-β in deep sites. Immunohistochemical markers were observed in the analyzed cells groups, both in deep and shallow sites, without significant differences between them. In the comparative analysis between immunohistochemical markers and GCF, IL-1-β showed high concordance in shallow and deep sites. Conclusions: The use of a standardized punch of 2 mm diameter for periodontal tissue biopsies seems to be suitable for immunohistochemistry analysis and showed that the GCF may not express all the markers in the same proportion at the corresponding tissue.